A Multifaceted Intervention to Improve Patient Knowledge and Safe Use of Opioids: Results of the ED EMC2 Randomized Controlled Trial. (19th November 2019) - McCarthy, Danielle M.; Curtis, Laura M.; Courtney, D. Mark; Cameron, Kenzie A.; Lank, Patrick M.; Kim, Howard S.; Opsasnick, Lauren A.; Lyden, Abbie E.; Gravenor, Stephanie J.; Russell, Andrea M.; Eifler, Morgan R.; Hur, Scott I.; et al.
Abstract: Objectives: Despite increased focus on opioid prescribing, little is known about the influence of prescription opioid medication information given to patients in the emergency department (ED). The study objective was to evaluate the effect of an Electronic Medication Complete Communication (EMC 2 ) Opioid Strategy on patients' safe use of opioids and knowledge about opioids. Methods: This was a three‐arm prospective, randomized controlled pragmatic trial with randomization occurring at the physician level. Consecutive discharged patients at an urban academic ED (>88, 000 visits) with new hydrocodone‐acetaminophen prescriptions received one of three care pathways: 1) usual care, 2) EMC 2 intervention, or 3) EMC 2  + short message service (SMS) text messaging. The ED EMC 2 intervention triggered two patient‐facing educational tools (MedSheet, literacy‐appropriate prescription wording [Take‐Wait‐Stop]) and three provider‐facing reminders to counsel (directed to ED physician, dispensing pharmacist, follow‐up physician). Patients in the EMC 2  + SMS arm additionally received one text message/day for 1 week. Follow‐up at 1 to 2 weeks assessed "demonstrated safe use" (primary outcome). Secondary outcomes including patient knowledge and actual safe use (via medication diaries) were assessed 2 to 4 days and 1 month following enrollment. Results: Among the 652 enrolled, 343 completed follow‐up (57% women; mean ± SD age = 42 ± 14.0 years). Demonstrated safe opioid use occurred more often in the EMC 2 group (adjusted odds ratio [aOR] = 2.46, 95% confidence interval [CI] = 1.19 to 5.06), but not the EMC 2  + SMS group (aOR = 1.87, 95% CI = 0.90 to 3.90) compared with usual care. Neither intervention arm improved medication safe use as measured by medication diary data. Medication knowledge, measured by a 10‐point composite knowledge score, was greater in the EMC 2  + SMS group (β = 0.57, 95% CI = 0.09 to 1.06) than usual care. Conclusions: The study found that the EMC 2 tools improved demonstrated safe dosing, but these benefits did not translate into actual use based on medication dairies. The text‐messaging intervention did result in improved patient knowledge.